ERGONOMY IN MINING: CONTRIBUTION FOR WORKER HEALTH PROMOTION (Fiep Bulletin - online, 2014)
Objectives: To identify the specialized theoretical production profile over the ergonomy in mining, verify the contributions of ergonomy to health promotion of mining activity workers and investigate the suggestions proposed for work general aspects improvement. Method: An Integrative Review of the Literature searches performed from the Search Portal in the Virtual Health Library, using the association between Descriptors in Health Sciences: ergonomics and mining. Altogether, 21 references were found, of which 10 met the inclusion criteria. Results: 60% (n=6) were available on the Index Medicus of the National Library of Medicine (MedLine), 60% (n=6) in the english language, 20% (n=2) were published in Occupational Medicine (London) and 30% (n=3) were characterized as search section. Furthermore, studies have shown that the ergonomic analysis leads to the identification of the reality experienced by employees, which allows intervene appropriately, and ergonomics identified as the most viable alternative. Conclusion: Ergonomics is perceived as a strategy that enables the management and prophylactic therapy appropriate to minimize the harmful effects of pathologies related to work in the mining industry.
Keywords: Work; Mining; Ergonomy.